Visual storytelling : character illustration for Chinese Mohist culture and technology : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Wang, Han (Massey University, 2024)
In the modern era of rapid information development, visual storytelling presented through graphic novels has become an engaging form of cultural communication. Visual stories have the capacity to convey profound meanings in Chinese moral vision and life wisdom. This design project develops new character illustrations to convey a story that promotes greater understanding of the Mohist culture and technology in the worlds of historical and future China. Illustration work for a proposed graphic novel aims to create visually engaging characters for a story that represents the history, culture, and technology of the Mohist School in a way that is easily understood by younger people and reflects on boundaries between modern technology and humanity.
Copyright holders of copyrighted images are invited to use the "Take Down Request Button" below to request their removal.
Keywords: 330316 Visual communication design (incl. graphic design); 360201 Creative writing (incl. scriptwriting)